Synchronous spindle cell Sarcoma of Sternum and left breast invasive Carcinoma: a case report - Haroon, Raihanah; Roslan, Muhammad Akram; Che Mohamed, Siti Kamariah; Md Ralib @ Md Raghib, Ahmad Razali; Abd. Fuaat, Azliana (2021)
The sternum is a critical structure of anterior chest wall but is an uncommon site for neoplastic involvement. Speedy diagnosis and treatment of sternal neoplasia is prudent to prevent circulatory collapse from mass effect to the mediastinum. When a new sternal mass is encountered, whether it is believed to be primary or secondary; malignancy needs to be considered until proven otherwise since primary sternal tumour is more frequently malignant than benign. Sternal chondrosarcoma is the most common; followed by myeloma, lymphoma and osteosarcoma. Spindle cell sarcoma of the sternum is very rare, while invasive breast carcinoma remains the most common form of breast cancer. However, synchronous occurrence of sternal spindle cell sarcoma and invasive breast carcinoma is extraordinary. Contrastingly, in the setting of a highly suspicious breast mass encountered with a concurrent sternal mass, skeletal metastasis to the sternum is usually the first differential diagnosis to consider though this is also uncommon. We report a 62-year-old lady with underlying diabetes mellitus and hypertension, presented with a hard central chest wall swelling for 4- months duration, described as increasing in size. Further clinical examination revealed a hard, immobile sternal mass. Incidentally a small left breast lump was also palpable, whereby subsequent mammogram and breast sonography depicted as a BIRADS 5 mass. Histopathological examination of the sternal mass biopsy depicted a spindle cell sarcoma; while that of the left breast biopsy revealed an invasive carcinoma. Patient underwent left mastectomy, axillary clearance, sternal tumour resection and chest wall reconstruction.